Anak dalam Kecepatan: Eksplorasi Syndrome Velocity dan Pengaruhnya terhadap Siswa SD Islam Nahdlatul Ulama - Elvira, Cindy; Surawan, Surawan (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
In the rapidly evolving digital era, elementary school children are increasingly exposed to social media trends such as velocity a video editing technique that creates rhythmic acceleration effects. This article explores the phenomenon of syndrome velocity, a psychosocial condition arising from academic pressure, social expectations, and intense digital exposure, which leads to emotional acceleration and diminished learning focus in children. Using a descriptive qualitative approach, the study combines literature review with interviews conducted with teachers and education staff at Nahdlatul Ulama Islamic Elementary School in Palangka Raya. The findings reveal that although only a portion of students actively participate in the velocity trend, its social and psychological impact extends across the classroom. This phenomenon affects students’ learning motivation, concentration, and emotional development. The study underscores the crucial role of families and schools in creating a balanced learning environment and promoting digital literacy so that children can manage social media exposure wisely.